Validated chromatographic methods for the simultaneous determination of Mometasone furoate and Formoterol fumarate dihydrate in a combined dosage form - Hanan A. Merey; Sally S. El-Mosallamy; Nagiba Y. Hassan; Badr A. El-Zeany (Faculty of Pharmacy, Cairo University, 2016)
Two chromatographic methods were developed and validated for the simultaneous determination of Mometasone furoate (MO) and Formoterol fumarate dihydrate (FOR). Combination of MO and FOR is used for the treatment of asthma in patients suffering from reversible obstructive airway disease. The first chromatographic method was based on using aluminum TLC plates pre-coated with silica gel GF254 as the stationary phase and chloroform:ethyl acetate:methanol:toluene:formic acid (5:2:2:2:0.1, by volume) as the mobile phase followed by densitometric measurement of the separated bands at 233 nm. The second method is a high performance liquid chromatographic method for the separation and determination of MO and FOR using reversed phase C18 column with isocratic elution. The mobile phase composed of methanol: 0.5% ammonium acetate pH adjusted with acetic acid (80:20, v/v) at a flow rate of 1.0 mL/min. Quantitation was achieved with UV detection at 220 nm. The specificity of the developed methods was investigated by analyzing the pharmaceutical dosage form. The validity of the proposed methods was assessed using the standard addition technique. The obtained results were statistically compared with those obtained by the reported methods, showing no significant difference with respect to accuracy and precision at p = 0.05.